Judd-Ofelt and McCumber Studies of Er3+ Ions Doped in Lanthanum Borate Glass for Visible and NIR Lighting Application. Issue 1 (28th March 2022) - Jarucha, N.; Ruangtaweep, Y.; Wantana, N.; Sangwaranatee, N.; Kedkaew, C.; Kaewkhao, J.
Abstract: The lanthanum borate glasses doped with Er 3+ were prepared by the melt-quenching technique to study the physical and luminescence properties. The glass composition in this study is 27.5La2 O3 -(72.5-x)B2 O3 -xEr2 O3, where x = 0, 1, 2, 3, 4, 5, 6 and 7 mol%. The results showed that the doping of Er2 O3 ions with more concentration increased glass density, molar volume, and refractive index. Absorbed photons with 388 nm can excite the glass samples to release the strongest emission at 530 nm wavelength. The suitable concentration of adding Er 3+ ions into La2 O3 -B2 O3 glass showed strongest light emission at 5 mol% concentration of Er2 O3 . NIR luminescence spectra was studied under 978 nm excitation wavelength of Er 3+ doped La2 O3 -B2 O3 glass. NIR emission peak was centered at 1544 nm. The Judd-Ofelt (JO) Ωλ (λ = 2, 4, and 6) parameters were calculated to explore the nature of environment surrounding the Er 3+ ions. Absorption and stimulated emission cross-sections have been evaluated by applying Mc Cumber theory, the resulting value is 8.25 × 10 −21 cm 2 . This research is beneficial for use as a NIR laser media in solid state emitting wavelength at 1544 nm. The optical gain G(λ) properties have been derived from the σabs and σemi values that the gain is positive for 40% population inversion in the 1400-1700 nm wavelength range.